Pathophysiological mechanisms of sepsis-associated acute kidney injury in children - Yu. V. Bykov (Translational Medicine, 2026)
The aim of this review was to systematize current pathophysiological mechanisms of sepsis-associated acute kidney injury (SA-AKI) in children and their relevance for early recognition of renal dysfunction. A review of 44 literature sources, published predominantly between 2021 and 2026, was conducted. SA-AKI cannot be explained solely by arterial hypotension or reduced renal perfusion. Its pathogenesis involves systemic inflammation, endothelial dysfunction, endothelial glycocalyx damage, intrarenal microcirculatory disturbances, coagulopathy, mitochondrial insufficiency, and inflammatory-metabolic injury to the tubular epithelium. Even after macrohemodynamic stabilization, capillary stasis, local hypoxia, interstitial edema, and heterogeneous renal perfusion may persist. Glycocalyx degradation increases vascular permeability, leukocyte-platelet adhesion, and microthrombus formation. Impaired fatty-acid β-oxidation, reduced mitochondrial ATP synthesis, oxidative stress, and altered phospholipid metabolism contribute to tubular dysfunction before a marked rise in serum creatinine. Complement and inflammasome activation, apoptosis, pyroptosis, necroptosis, ferroptosis, and disturbances of autophagy, mitophagy, and tissue repair play a distinct role in sustaining renal injury. In newborns and young children, these mechanisms are important because of immature immune and vascular regulation, susceptibility to fluid overload, and limited functional renal reserve. The delayed rise in creatinine and the variable diagnostic value of urine output restrict early detection; therefore, risk assessment should consider age, baseline renal reserve, fluid exposure, and the severity of multiple organ dysfunction. SA-AKI should be regarded as an early manifestation of profound tissue dysregulation rather than only as a late laboratory complication of sepsis.